The Analysis of Factors Affecting Delay and Absenteeism of 12th Grade Students at SMA Katolik Sint Carolus Penfui Kupang for the 2025/2026 Academic Year (A Case Study of Guidance and Counseling) - Bere, Maria Teresa Febrianty; Nagul, Wens (The Future of Education Journal, 2026)
This study aims to analyze the factors influencing tardiness and absenteeism of student YN in Grade XII C at Sint Carolus Catholic Senior High School, Penfui, Kupang, during the 2025/2026 academic year. The research employed a qualitative approach using a guidance and counseling case study method. Data were collected through classroom observations, interviews with the homeroom teacher, subject teachers, and the guidance and counseling teacher, as well as documentation analysis in the form of daily attendance records. Data analysis was conducted through problem identification, diagnosis, prognosis, therapeutic intervention, and the formulation of conclusions and follow-up actions. The findings indicate that the student’s tardiness and absenteeism were caused by a combination of internal and external factors. Internal factors included laziness, low learning motivation, poor time management skills, and a tendency to stay up late due to excessive gaming. External factors comprised negative peer influence, a lack of parental supervision and attention, and the relatively long distance between the student’s home and the school. The impact of these problems was reflected in decreased academic achievement, reduced concentration during learning activities, undisciplined behavior, and less harmonious relationships with teachers and classmates. Intervention was carried out through individual counseling services using a self-management technique, along with educational guidance on time management, self-control, and the selection of positive peer environments. The evaluation results showed initial improvements in the student’s self-awareness and sense of responsibility toward school tasks; however, further development requires continuous assistance and collaboration among the guidance counselor, homeroom teacher, and parents. This study emphasizes that students’ learning discipline is the result of an interaction between personal and environmental factors and therefore requires an integrated approach for effective resolution.